Telaah Struktural Hermeneutik Kisah Nabi Ibrahim dalam Alquran - Nadia, Zunly (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2020)
This paper attempts to analyze the Qur’anic story of Ibrahim in the light of hermeneutical structuralism. It aims at unrevealing the meaning through its relational features of the language structure in each verse. Besides, the hermeneutical approach complements to our understanding on the text in a non-structural symbolic interpretation. By these two approaches, this paper finds a paralleled analogy between the moon, stars and sun with the statue and Namrud. The relationship between these things was evident from the point that the three were considered to be gods but no one could prove their qualities possessed by God. Another parallel was apparent from the logic of the birds, fire and goats. As Ibrahim has experienced several extraordinary events in his life, these events can be found paradigmatic relations that all of them are in the frame of sacrifice, preaching, and efforts to call people on the faith in God.